PolyRec Gesture Design Tool: A tool for fast prototyping of gesture‐based mobile applications. (13th September 2021) - Bufano, Roberto; Costagliola, Gennaro; De Rosa, Mattia; Fuccella, Vittorio
Abstract: In this article, we present PolyRec Gesture Design Tool (PolyRec GDT ), a tool that allows the definition of gesture sets for mobile applications. It supports the entire process of designing gesture sets, from collecting gestures to analyzing and exporting the set created for use in a mobile application. It is equipped with the PolyRec gesture recognizer, a unistroke recognizer based on template matching with good accuracy and performances while still allowing support for other recognizers. The main features of PolyRec GDT include the ability to collect gestures directly on mobile devices, to detect similarities between gestures to help the designer to detect ambiguities in the design phase, and the ability to automatically select the most representative gestures for each gesture class by using a clustering technique to increase recognition speed without affecting accuracy. Experimental results show that this latter feature allows an increase in accuracy compared with when the same operation is performed manually by developers or randomly by software. Finally, a user study was carried out to evaluate PolyRec GDT, in which participants were asked to use it to add gesture functionality to a mobile application. The results showed that with the support of PolyRec GDT this operation took only a few minutes for participants with mobile development experience, whereas it would have taken much longer without the support of PolyRec GDT .